2006
DOI: 10.1523/jneurosci.5045-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Lighter or Heavier Than Predicted: Neural Correlates of Corrective Mechanisms during Erroneously Programmed Lifts

Abstract: A central concept in neuroscience is that the CNS signals the sensory discrepancy between the predicted and actual sensory consequences of action. It has been proposed that the cerebellum and parietal cortex are involved in this process. A discrepancy will trigger preprogrammed corrective responses and update the engaged sensorimotor memories. Here we use functional magnetic resonance imaging with an event-related design to investigate the neuronal correlates of such discrepancies. Healthy adults repeatedly li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
88
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 44 publications
7
88
0
Order By: Relevance
“…Even though our data are in good agreement with the current mirror neuron theory, an alternative, not mutually exclusive interpretation can be that the experimental context activated movement representations in terms of stored internal models (Bursztyn, Ganesh, Imamizu, Kawato, & Flanagan, 2006;Jenmalm, Schmitz, Forssberg, & Ehrsson, 2006). More specifically, experiment 2 showed that the presentation of tension/pressure cues on grip force was sufficient to mediate force-related activity within the observer's M1.…”
Section: Functional Significance and Potential Mechanisms Underlying supporting
confidence: 81%
See 1 more Smart Citation
“…Even though our data are in good agreement with the current mirror neuron theory, an alternative, not mutually exclusive interpretation can be that the experimental context activated movement representations in terms of stored internal models (Bursztyn, Ganesh, Imamizu, Kawato, & Flanagan, 2006;Jenmalm, Schmitz, Forssberg, & Ehrsson, 2006). More specifically, experiment 2 showed that the presentation of tension/pressure cues on grip force was sufficient to mediate force-related activity within the observer's M1.…”
Section: Functional Significance and Potential Mechanisms Underlying supporting
confidence: 81%
“…More specifically, similar to the way that the sight of an object can recruit internal models for scaling the forces needed to handle the object ) the sight of different levels of hand contraction may have induced the activation of stored internal motor representations for scaling the observed isometric forces. In this respect, the elicited M1 responses might have been driven by other pathways than those predicted by the mirror neuron theory, potentially involving the cerebellum (Bursztyn et al, 2006;Jenmalm et al, 2006).…”
Section: Functional Significance and Potential Mechanisms Underlying mentioning
confidence: 93%
“…Weight changes led to increased activity in the right inferior parietal cortex [Jenmalm et al (2006) (Desmurget et al, 1999). Together, these data and the location and connectivity of this region, receiving input from sensory cortices and having output connections to the motor regions, make it a good candidate for "comparator region.…”
mentioning
confidence: 91%
“…Jenmalm et al (2006) have made a significant contribution to this topic using functional magnetic resonance imaging in a study recently published in the Journal of Neuroscience.…”
mentioning
confidence: 99%
See 1 more Smart Citation